Durabilidade de vigas de concreto armado reforçadas com mantas de CFRP submetidas a degradação acelerada - Sarti Junior, Luiz Antônio (2020)
Currently, as an alternative to reinforced concrete structures, which have suffered physical or chemical degradation, strengthening systems have been used which use composite materials. Composites are formed by combining two or more types of non-soluble materials. In this sense, the most used strengthening technique is EBR (Externally Bonded Reinforcement), in which it is applied directly to the concrete substrate of the element to be strengthened. The long-term behavior of strengthening systems based on composite materials is still little known. In this context, the present study employs the accelerated conditioning protocol proposed by the american code ACI 440.9R (ACI, 2015), to evaluate the durability of strengthening systems, without protection, applied in reinforced concrete beams. 12 reinforced concrete beams were produced with a 12 x 20 cm2 rectangular section, 0.75 % longitudinal reinforcement rate and machined concrete with a compressive strength of 32 MPa. Of the set of 12 beams, 6 were strengthened with flexion using CFRP (Carbon Fiber Reinforced Polymer) applied according to the EBR technique. In addition, epoxy resin specimens and CFRP composites were produced, using the same materials that make up the strengthening systems applied to reinforced concrete beams, which were maintained and tested in the same pre-defined environments and ages for the beams. Among the set of 12 beams, 4 were adopted as “reference”, of which two were not strengthened in CFRP and two were strengthened’. The rest were divided into two groups and exposed for 1000 hours in the laboratory and accelerated degradation. As a way of evaluating the possible degradation of the strengthening systems, after the predefined exposure period, mechanical flexion tests were conducted with load application in the middle of the beams. The analysis of the results was carried out in a comparative way; thus, it was evaluated the degradation that the exposure for 1000 hours to the accelerated conditioning protocol provided the beams, and then, it was compared with the results obtained for the reference beams. Subsequently, the results obtained with the accelerated degradation, of the reinforced concrete beams, were compared with those obtained in an experimental program, similar to the one of the present study, however in this the degradation environment was the natural weathering for 6 months. The results showed that epoxy adhesives show statistically different reductions in their mechanical properties, while CFRP composites showed small changes after exposure to the analyzed environments. It was also found that the strengthening systems provides large increases in load capacity and rigidity in strengthened reinforced concrete beams. However, correlating the results obtained after an accelerated degradation cycle lasting 1000 hours (42 days) with the tests carried out after 6 months of exposure to the weather, it was observed that both showed a reduction of approximately 10 % of the load capacity of the strengthened elements, indicating the degradation of the strengthening systems. Thus, it was found that 1000 hours of exposure to accelerated degradation, constant humidity with controlled temperature, is equivalent to 6 months of exposure to weathering.